The relationship between magnesium and seizure control in epileptic patients - Suparman, Yonathan A.; Khosama, Herlyani; Mahama, Corry N. (International Journal of Research in Medical Sciences, 2021)
Background: Magnesium has a central nervous system depressant effect by inhibiting the N-methyl-D-aspartate (NMDA) receptor, an antagonist of calcium channels, and increasing the surface tension of the cell membrane. Patients with epilepsy who had seizures more than 4 times/week had lower serum magnesium levels than those with the episode of less than or equal to 1 time/week. A low dose of magnesium added to phenytoin or carbamazepine can reduce seizure frequency. We want to evaluate the relationship between serum magnesium levels and their dietary intake level with seizure control in Manado. Methods: Patients with epilepsy aged 18-65 years, from July 2019 to October 2019, were tested for dietary and serum magnesium level in the last 30 days using NutriSurvey software. Regression models were used to quantify the relationship between dietary and serum magnesium level with seizure freedom and its frequency in the last 30 days. Results: One hundred and ten epileptic patients were included in this study. The median serum magnesium level is 2 mg/dl. There was no significant relationship between serum magnesium levels and seizure freedom (p=0.423) or its frequency in the last 30 days (p=0.966). Dietary magnesium intake (OR 1.01; 95% CI 1.00-1.02, p=0.034) was associated with seizure freedom but not with its frequency (p=0.423). Conclusions: Dietary magnesium intake was associated with seizure freedom, but serum magnesium levels were not associated with seizure freedom or frequency.